Effects of systemic inflammation due to hepatic ischemia-reperfusion injury upon lean or obese visceral adipose tissue - Ferraz,Ligia Fernanda (2022)
ABSTRACT Purpose: To evaluate how the induction of liver damage by ischemia and reperfusion affects the adipose tissue of lean and obese mice. Methods: Lean and diet-induced obese mice were subjected to liver ischemia (30 min) followed by 6 h of reperfusion. The vascular stromal fraction of visceral adipose tissue was analyzed by cytometry, and gene expression was evaluated by an Array assay and by RT-qPCR. Intestinal permeability was assessed by oral administration of fluorescein isothiocyanate (FITC)-dextran and endotoxemia by serum endotoxin measurements using a limulus amebocyte lysate assay. Results: It was found that, after liver ischemia and reperfusion, there is an infiltration of neutrophils, monocytes, and lymphocytes, as well as an increase in the gene expression that encode cytokines, chemokines and their receptors in the visceral adipose tissue of lean mice. This inflammatory response was associated with the presence of endotoxemia in lean mice. However, these changes were not observed in the visceral adipose tissue of obese mice. Conclusions: Liver ischemia and reperfusion induce an acute inflammatory response in adipose tissue of lean mice characterized by an intense chemokine induction and leukocyte infiltration; however, inflammatory alterations are already present at baseline in the obese adipose tissue and liver ischemia and reperfusion do not injure further.